1301 Lactobacillus spp. act in synergy to attenuate splenomegaly and lymphadenopathy in lupus- prone MRL/lpr mice. (14th December 2022) - Cabana-Puig, Xavier; Mu, Qinghui; Lu, Ran; Swartwout, Brianna; Abdelhamid, Leila; Zhu, Jing; Prakash, Meeta; Cecere, Thomas E; Wang, Zhuang; Callaway, Sabrina; Sun, Sha; Reilly, Christopher M; et al.
Abstract : Commensal bacteria and the immune system have a close and strong relationship that maintains a balance to control inflammation. Alterations of the microbiota, known as dysbiosis, can direct reactivity to self-antigens not only in the intestinal mucosa but also at the systemic level. Our laboratory previously reported gut dysbiosis, particularly lower abundance of bacteria in the family Lactobacillaceae, in lupus-prone MRL/ lpr mice, a model of systemic autoimmunity. Restoring the microbiota with a mix of 5 different Lactobacillus species (spp.), L. reuteri, L. oris, L. johnsonii, L. gasseri and L. rhamnosus, attenuated lupus-liked clinical signs, including splenomegaly and lymphadenopathy. However, our understanding of the mechanism was limited. In this study, we used the lupus-prone MRL/ lpr mouse model to delineate the mechanisms through which Lactobacillus spp. modulate lupus pathogenesis. We first investigated the effects of individual species. Surprisingly, none of the species individually recapitulated the benefits of the mix. Instead, Lactobacillus spp. acted synergistically to attenuate splenomegaly and renal lymphadenopathy through secreted factors and a CX3 CR1-dependent mechanism. Interestingly, oral administration of MRS broth exerted the same benefits likely through increasing the relative abundance of endogenous Lactobacillus spp. Mechanistically, we found increased percentages of FOXP3-negative type 1 regulatory T cells with administration of the mix in both spleen and mesenteric lymph nodes. In addition, oral gavage of Lactobacillus spp. decreased the percentage of central memory T cells while increasing that of effector memory T cells in the lymphoid organs. Furthermore, a decreased percentage of double negative T cells was observed in the spleen with the mix. These results suggest that Lactobacillus spp. might act on T cells to attenuate splenomegaly and lymphadenopathy. Together, this study advances our understanding of how Lactobacillus spp. attenuate lupus in MRL/ lpr mice. The synergistic action of these bacteria suggests that multiple probiotic bacteria in combination may dampen systemic autoimmunity and benefit lupus patients.